Urgent Surgery for A Month-Long Headache: a Case Report - Erkan Gunay (Saudi Journal of Emergency Medicine)
Traumatic brain injury (TBI) is defined as impaired brain function due to external force. In the adult population threated at the Emergency Department (ED) prevalence is twice as high in males then females. It is classified as mild moderate and severe based on Glasgow Coma Scale (GCS). Subdural Hematomas (SDH) are generally associated with high-energy traumas, especially road accidents and mostly seen amongst the population aged [SJEMed 2024; 5(1.100): S47-S47]